Magnitude-based inference: What is it? How does it work and is it appropriate? - Van Hooren, B. (Sport Performance & Science Reports, 2018)
Research in the field of sports science is frequently performed on a relatively small number of individuals. We are usually however interested in knowing whether the effect found in our sample of individuals also applies to a larger group: the population from which the sample is drawn. For this purpose, we use statistical inferential methods. There are several statistical inferential methods available. The most widely used method is arguably null-hypothesis significance testing. This method has been widely criticized since its introduction, most prominently because statistically signi cant results are not necessarily clinically relevant and statistically non-signi cant results can still be clinically relevant (Figure 1). (1, 2) Magnitude-Based Inference. Motivated by the limitations of null-hypothesis signi cance testing, Batterham and Hopkins (1) developed a new statistical inferential method in 2006 entitled \Magnitude-Based Inference". In this method, confidence intervals are interpreted in relation to a smallest worthwhile change (Figure 1). The method has seen a large uptake in the sports science community and is also increasingly used in other research elds. Despite this large uptake, not all researchers and practitioners fully understand how the method works. Understanding how Magnitude-Based Inference works is however important as it helps researchers and practitioners to correctly interpret the results of studies that have used this method. In a new video, I therefore explain what Magnitude-Based Inference is and how it works.